Integrating priorities of disadvantaged parents and professionals for community family health. (13th November 2019) - Wink, G; Fransen, G A J; Huisman, M J; Boersma, S N; Assendelft, W J J; Wagemakers, M A E; van der Velden, J; van den Muijsenbergh, METC
Abstract: Background: Health inequalities persist, and policymakers, researchers and practitioners seek for effective ways to positively impact the health of disadvantaged people. Researchers point to a multi-component program with an integral design including various perspectives and involving different stakeholders. Few studies address the perspectives on health of disadvantaged people themselves. This study describes what parents in a socially disadvantaged situation and professionals working in that community perceived as 1) priority aspects to improve family health 2) barriers and facilitators for health behaviour changes 3) important health program activities. Methods: Design: Community-based participatory action research. 10 parents participated in 6 panel meetings. 46 professionals received 4 panel meetings summaries. 18 parents and 25 professionals responded to questions in (panel) meetings and consultation by phone and e-mail. Results: (preliminary) 1) Parents' top priorities for improving health were: less stress related to finances and communication with related organizations, followed by a safe place for kids to meet. Of the program financers' aims (reducing tobacco, alcohol use and overweight) reducing overweight got relatively most support of parents. 2) Parents perceived their family financial situation as barrier to behaviours reducing stress and overweight. 3) Program activities related to reducing stress got more support from parents and professionals than activities related to reducing overweight. Conclusions: Insight in the perspectives of disadvantaged parents and professionals resulted in a program plan supported by them, aiming to reduce stress and overweight. Most participating parents and professionals committed themselves to invest time in program activities execution. Key messages: Disadvantaged parents perceived reducing stress related to finances as top priority to improve family health. They perceived family finances as barrier to behaviours reducing stress and overweight. Community-based participatory action research with disadvantaged parents and professionals can result in an integrated family health program plan with stakeholder support.